2023
DOI: 10.3390/molecules28155766
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Members of the Chemokine Family as a Novel Approach to Treating Neuropathic Pain

Abstract: Neuropathic pain is a debilitating condition that affects millions of people worldwide. Numerous studies indicate that this type of pain is a chronic condition with a complex mechanism that tends to worsen over time, leading to a significant deterioration in patients’ quality of life and issues like depression, disability, and disturbed sleep. Presently used analgesics are not effective enough in neuropathy treatment and may cause many side effects due to the high doses needed. In recent years, many researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 348 publications
0
5
0
Order By: Relevance
“…Although, its levels are highest in microglia/macrophages [57,132,[240][241][242][243][244]. CCR2 is preferentially bound by CCL2 [245]; however, several other chemokines, CCL7, CCL8, CCL12, and CCL13 (please see Table 1), can also bind to this receptor [37,239,245,246]. Importantly, CCR2 activation promotes angiogenesis [247] and fracture healing [248] and decreases amyloid plaque formation in Alzheimer's disease models through macrophage-mediated phagocytosis [249,250].…”
Section: Ccr2-ligands and Pharmacological Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, its levels are highest in microglia/macrophages [57,132,[240][241][242][243][244]. CCR2 is preferentially bound by CCL2 [245]; however, several other chemokines, CCL7, CCL8, CCL12, and CCL13 (please see Table 1), can also bind to this receptor [37,239,245,246]. Importantly, CCR2 activation promotes angiogenesis [247] and fracture healing [248] and decreases amyloid plaque formation in Alzheimer's disease models through macrophage-mediated phagocytosis [249,250].…”
Section: Ccr2-ligands and Pharmacological Modulationmentioning
confidence: 99%
“…Further research is needed to determine why this is possible, but it is already known that excessive production of interleukins, such as IL-1β and IL-18, might be key for reducing opioid analgesia in neuropathy [215,216,275]. Several studies have indicated that opioid signaling is connected not only to interleukins but also to chemokines [37,246]. CCR2 is preferentially bound by CCL2 [245], but repeated administration of morphine increases the level of CCL2 in the spinal cord; however, its neutralization by an antibody diminishes the development of morphine tolerance [276].…”
Section: Ccr2-pharmacological Modulationmentioning
confidence: 99%
“…In a ttw mice model, in vivo depletion of CCL2 in microglia mitigated the severity of chronic spinal compression and related pain (11). In contrast, both INCB3344 and RS504393, specific antagonists of CCR2, improve the CCL-induced nociceptive sensitization (12,13). Altogether, these studies indicate that CCL2/CCR2 signaling pathway plays an important role in the occurrence and/or persistence of pain.…”
mentioning
confidence: 96%
“…21 Targeting CCR4 also represents a promising strategy for the treatment of neuropathic pain. 22 Two chemotypes of selective CCR4 NAMs have been identified by random screening that bind to distinct receptor sites. 23 The first chemotype includes basic small lipophilic antagonists (e.g., BMS-397 and Z5367428075), which are predicted to bind to the extracellular side of the receptor, partially overlapping with the orthosteric site.…”
mentioning
confidence: 99%
“…It is implicated in cancer pathogenesis and allergic diseases including asthma and dermatitis . Targeting CCR4 also represents a promising strategy for the treatment of neuropathic pain . Two chemotypes of selective CCR4 NAMs have been identified by random screening that bind to distinct receptor sites .…”
mentioning
confidence: 99%